Green Tea Polyphenol Catechins Inhibit Coronavirus Replication and Potentiate the Adaptive Immunity and Autophagy-Dependent Protective Mechanism to Improve Acute Lung Injury in Mice - Chih-Ching Yang; Chang-Jer Wu; Chen-Yen Chien; Chiang-Ting Chien (MDPI AG, 2021)
Effective antiviral therapeutics are urgently required to fight severe acute respiratory syndrome (SARS) caused by a SARS coronavirus (SARS-CoV). Because polyphenol catechins could confer antioxidative, anti-inflammatory, antiviral, and antimicrobial activities, we assessed the therapeutic effects of catechins against SARS-CoV replication in Vero E6 cells, the preventive effect of catechins on CD25/CD69/CD94/CD8+ cytotoxic T lymphocytes-mediated adaptive immunity, and the protective effect on lipopolysaccharide-induced acute lung injury (ALI) in mice. We found that catechins containing 32.8% epigallocatechin gallate, 15.2% epicatechin gallate, 13.2 epicatechin, 10.8% epigallocatechin, 10.4% gallocatechin, and 4.4% catechin directly inhibited SARS-CoV replication at sub-micromolecular concentrations. Four-week catechins ingestion increased CD8+ T cell percentage, upregulated CD69+/CD25+/CD94-NKG2A/CD8+ T lymphocytes-mediated adaptive immunity, and increased type I cytokines release responding to ovalbumin/alum. Catechins significantly reduced lipopolysaccharide-induced cytokine storm and oxidative stress and ALI by inhibiting PI3K/AKT/mTOR signaling to upregulate Beclin-1/Atg5-Atg12/LC3-II-mediated autophagy mechanism. Pretreatment of autophagy inhibitor 3-Methyladenine reversed the inhibiting effects of catechins on the cytokines and oxidative stress levels and ALI. In conclusion, our data indicated that catechins directly inhibited SARS-CoV replication, potentiated the CD25/CD69/CD94/CD8+ T lymphocytes-mediated adaptive immunity and attenuated lipopolysaccharide-induced ALI and cytokine storm by PI3K/AKT/mTOR-signaling-mediated autophagy, which may be applied to prevent and/or treat SARS-CoV infection.